Efektivitas Program Foodcourt Berdaya dalam Meningkatkan Kesejahteraan Mustahik dalam pada Baitulmaal Muamalat Sulawesi Selatan - Ainiyyah, Fadillah Adella; Anwar, Nurfiah; Putra, Trisno Wardy (MASALIQ, 2023)
One of the arrangements for equal wages for muslims is trough zakat. Zakat is an obligation for muslims to give to thoses in need. This research aims to determine the empowered food court program carried out by Baiyulmaal Muamalat South Sulawesi Selatan the welfare of mustahik. The method used in this research is a qualitative method with a phenomenological approach. Based on the research results, the analysis regarding the effectiveness of the empowere food court program in improving in the welfare of mustahik is said to be ineffective. This can be seen from the efectiveness indicator used, there are 2 indicators that are not yet effective while the other 2 indicator are effective. It is said that the empowered foodcourt program has not been effective in improving the welfare of mustahik.